A firefly inspired game dissemination and QoS-based priority pricing strategy for online social network games. (2018) - Raj, Ebin Deni; Babu, L.D. Dhinesh
With almost all educated individuals having access to computing cum communication gadgets like mobiles, tablets, PCs, and laptops, online social networks (OSNs) have become the default means of networking among majority of individuals. OSNs have become an inseparable part of daily lives attracting more than one third of the current world population. Majority of the users enjoy the entertainment aspects of OSNs like gaming with friends from different geographic locations. Social gaming has spawned a whole new sub culture which helps users to discover and build connections with other users. Game development companies constantly try to publicise and attract new users using OSNs to enhance their revenues. In this context, we propose a new firefly inspired strategy to spread and disseminate games in OSNs and assist the gaming companies to decrease the acceptance-discontinuance anomaly. Collective behaviour in online social network is closely related to swarm intelligence techniques. We have also proposed a rewarding and efficient Firefly inspired QoS-based priority pricing model that will attract more users to play online games while using online social networks, thereby, enhancing the profits of the service providers and game developers.